A nonrandom subset of olfactory genes is associated with host preference in the fruit fly Drosophila orena. Issue 2 (1st June 2017) - Comeault, Aaron A.; Serrato-Capuchina, Antonio; Turissini, David A.; McLaughlin, Patrick J.; David, Jean R.; Matute, Daniel R.
Abstract: Specialization onto different host plants has been hypothesized to be a major driver of diversification in insects, and traits controlling olfaction have been shown to play a fundamental role in host preferences. A diverse set of olfactory genes control olfactory traits in insects, and it remains unclear whether specialization onto different hosts is likely to involve a nonrandom subset of these genes. Here, we test the role of olfactory genes in a novel case of specialization in Drosophila orena . We report the first population-level sample of D. orena on the West African island of Bioko, since its initial collection in Cameroon in 1975, and use field experiments and behavioral assays to show that D. orena has evolved a strong preference for waterberry ( Syzygium staudtii ). We then show that a nonrandom subset of genes controlling olfaction-–those controlling odorant-binding and chemosensory proteins–-have an enriched signature of positive selection relative to the rest of the D. orena genome. By comparing signatures of positive selection on olfactory genes between D. orena and its sister species, D. erecta we show that odorant-binding and chemosensory have evidence of positive selection in both species; however, overlap in the specific genes with evidence of selection in these two classes is not greater than expected by chance. Finally, we use quantitative complementation tests to confirm a role for seven olfactory loci in D. orena 's preference for waterberry fruit. Together, our results suggest that D. orena and D. erecta have specialized onto different host plants through convergent evolution at the level of olfactory gene family, but not at specific olfactory genes.